A Review on Anesthetic Drug Discovery with Computer Aided Drug Design - Satish Kumar Yadav; Mohd. Wasiullah; Piyush Yadav; Ankit Maurya; Mr. Sushil Yadav (International Journal of Antibiotics, 2024)
In contemporary medicine, anaesthesia is essential for enabling surgical procedures, pain control, and patient comfort. Finding and creating safe and efficient anaesthetics is crucial to enhancing patient outcomes and developing the medical field. In this review, we provide a comprehensive overview of anesthetic drug discovery with a focus on the integration of computer-aided drug design (CADD) methodologies. Beginning with an exploration of anesthesia mechanisms and targets, we delve into the principles of CADD, including molecular modeling, pharmacophore modeling, virtual screening, molecular docking, and quantitative structure-activity relationship (QSAR) modeling. Through case studies, we highlight successful applications of these computational approaches in lead identification, optimization, and rational drug design in the field of anesthesia. Additionally, we discuss the challenges and future directions in anesthetic drug discovery, including personalized medicine, artificial intelligence, multiomics approaches, drug delivery advancements, interdisciplinary collaboration, and ethical considerations. By leveraging the power of computational methodologies and interdisciplinary collaboration, we aim to accelerate the development of novel anesthetic agents with improved efficacy, safety, and patient outcomes.
Keywords: Anesthesia; Drug discovery; Personalized medicine; Virtual screening; artificial intelligence; computer-aided drug design; molecular docking; molecular modeling; pharmacophore modeling; quantitative structure-activity relationship (QSAR) modeling